2012
DOI: 10.1177/097215091201300206
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Announcement and Market Response in Indian Stock Market: An Event-Study Analysis

Abstract: Event study has remained one of the highly pursued areas of research in corporate finance. Studies reported in this realm empirically show that the economic model or the capital asset pricing model (CAPM) yields relatively better results with respect to the abnormal return of stocks preceded by dividend announcement by the dividend payers as compared to the statistical model, namely, constant return or market model approaches. Both models are incorporated in the study to triangulate the outcomes more accuratel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Renata et al (2017) based on market model of event study found the positive statistically insignificant AAR exist within the event. Maitra and Dey (2012) incorporated the CAPM model and market model separately to measure the market response of dividend announcement in Indian stock market. Bhattacharjee and De (2018) observed that the market reaction to firm-specific corporate news varies according to the type of new across different industry groups.…”
Section: Review and Literaturementioning
confidence: 99%
“…Renata et al (2017) based on market model of event study found the positive statistically insignificant AAR exist within the event. Maitra and Dey (2012) incorporated the CAPM model and market model separately to measure the market response of dividend announcement in Indian stock market. Bhattacharjee and De (2018) observed that the market reaction to firm-specific corporate news varies according to the type of new across different industry groups.…”
Section: Review and Literaturementioning
confidence: 99%
“…Thus, Indian firms can distribute their profits in the form of dividends and raise funds from capital markets at lower costs to meet their positive NPV projects requirements. It has been found that the firm’s dividend policy has greater implications for the firm’s performance such as profitability and stock market returns (Amidu, 2007; Maitra & Dey, 2012; Saravanakumar, 2011; Uwuigbe, Jafaru, & Ajayi, 2012).…”
Section: Rationale Of the Studiesmentioning
confidence: 99%
“…The study reports that dividend announcement conveys information to market traders. Using both capital asset pricing model (CAPM) and market model, Maitra and Dey (2012) observe that there are significant abnormal returns (positive or negative or both) upon dividend announcement which is more evident under the CAPM model. Campbell and Ohuocha (2011) examine whether stock dividend announcements create value for firms traded in the Nigerian Stock Exchange by using the standard event study methodology.…”
Section: Review Of Literaturementioning
confidence: 99%